Impact of Visual Emotional Advertising on Saudi Consumer Behavior Towards Shopping Goods in the Kingdom - Alshaibani , Majed Fahad; Helal , Ahmed H. (Journal of Posthumanism, 2025)
The current study aims to assess the impact of visual emotional advertising on Saudi consumer behavior regarding shopping goods in the Kingdom. The main objective encompasses three sub-goals focused on evaluating the effects of visual emotional advertising on consumer awareness, purchase decisions, and loyalty toward shopping goods in the Kingdom. The study population includes all Saudi consumers of shopping goods on the X platform, totaling 16.84 million people, or 45.3% of the projected population for 2024. A judgmental sampling method was used, with a minimum sample size set at 385 individuals, which was later increased to 600. The data collection tool was a fully structured questionnaire distributed via Google Drive, and all distributed questionnaires were successfully retrieved for final analysis. The study utilized a five-point Likert scale to measure the independent variable (visual emotional advertising) and the dependent variable (consumer behavior). The findings revealed that the application level of visual emotional advertising in shopping goods stores is moderate, as is the behavior of Saudi consumers towards these goods. Notably, the study found a highly positive impact of visual emotional advertising on Saudi consumer behavior regarding shopping goods. At the sub-hypothesis level, there is a significant positive effect of visual emotional advertising on all components of consumer behavior: awareness, purchasing decisions, and loyalty. The study concludes with several recommendations aimed at enhancing the implementation of visual emotional advertising within the Saudi business environment, particularly in shopping goods stores.